2021
DOI: 10.1002/chem.202003580
|View full text |Cite
|
Sign up to set email alerts
|

Organic Superbases in Recent Synthetic Methodology Research

Abstract: Organic superbases are a distinct and increasingly utilized class of Brønsted base that possess properties complementary to common inorganic bases. This Concept article discusses recent applications of commercial organic superbases in modern synthetic methodologies. Examples of the advantages of organic superbases in three areas are highlighted, including the discovery of new base‐catalyzed reactions, the optimization of reactions that require stoichiometric Brønsted base, and in high‐throughput experimentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 251 publications
(57 reference statements)
1
79
0
Order By: Relevance
“…The use of such bases is advantageous relative to strong inorganic bases (e.g., NaOtBu) that exhibit poor functional group tolerance, or weak inorganic bases (e.g., Cs 2 CO 3 ) that suffer from poor solubility and inconsistent reactivity profiles arising from particle size variation. [7] Notwithstanding the mechanistically innovative nature of these protocols, the substrate scope achieved by use of the above-cited [4][5][6] and other related photoredox/ electrochemical/reductant methods [8] is typically limited to electronically activated (hetero)aryl bromides paired with alkylamine, aniline, or sulfur-based (e.g., sulfonamide, [9] sulfamide, [10] sulfamate ester, [11] sulfoximine [12] ) nucleophiles. Absent from such reports is the general application of (hetero)aryl chloride or phenol derivatives, which represent the most attractive electrophile classes owing to their low cost and wide availability.…”
Section: Introductionmentioning
confidence: 99%
“…The use of such bases is advantageous relative to strong inorganic bases (e.g., NaOtBu) that exhibit poor functional group tolerance, or weak inorganic bases (e.g., Cs 2 CO 3 ) that suffer from poor solubility and inconsistent reactivity profiles arising from particle size variation. [7] Notwithstanding the mechanistically innovative nature of these protocols, the substrate scope achieved by use of the above-cited [4][5][6] and other related photoredox/ electrochemical/reductant methods [8] is typically limited to electronically activated (hetero)aryl bromides paired with alkylamine, aniline, or sulfur-based (e.g., sulfonamide, [9] sulfamide, [10] sulfamate ester, [11] sulfoximine [12] ) nucleophiles. Absent from such reports is the general application of (hetero)aryl chloride or phenol derivatives, which represent the most attractive electrophile classes owing to their low cost and wide availability.…”
Section: Introductionmentioning
confidence: 99%
“…Brief reaction analysis revealed that an oxygen transfer reagent and boron source were required for the expected deoxy-borylation. Recent efforts in our laboratory 29 , 30 and others’ 31 40 suggested that diboron reagents, in concert with some Lewis bases 41 , could serve both purposes. Specifically, some earlier discoveries from Aggarwal’s 24 , 33 , 40 , Glorius’s 34 , Studer’s 35 , 39 , Shi’s 36 and our groups 30 unveiled a unique diboron reagent, bis(catecholato)diboron (B 2 cat 2 ), that could effect the reductive borylation of various carbon electrophiles under metal-free conditions.…”
Section: Resultsmentioning
confidence: 97%
“…Their particular atomic architecture with two or three N atoms bonded to the same C‐ sp 2 contributes to stabilizing its conjugated acid. Thus, these compounds present the highest measured proton affinities and they are well‐known to be superbases [57] (superbases, by definition, [49] show PA values larger than 1027 kJ mol −1 ). Most of the ACA‐complexes involving these bases were not located except those formed with the tertiary alkylammonium cation Me 3 NH + with TACA values between 131.9 and 154.4 kJ mol −1 (see green points, Figure 8, up).…”
Section: Resultsmentioning
confidence: 99%
“…N-sp 2 organobases The organobase family with an interacting N-sp 2 atom was split into five categories: azoles (13)(14)(15)(16)(17)(18)(19)(20)(21)(22); azines (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36); amidines (37)(38)(39)(40)(41)(42)(43); guanidines (44)(45)(46)(47)(48) and azapolycycles (49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61). We start commenting the selected azoles and azines (Figure 5).…”
mentioning
confidence: 99%